Շախմատային նախագիտելիքի ճանաչողական գործառույթները նախադպրոցական կրթության մեթոդիկաներում - Ամիրաղյան, Մ. Գ. (Մանկավարժ հրատ․)
Հոդվածում քննարկվում է նախադպրոցական կրթության մեթոդիկաների լրամշակման խնդիրը՝ ավագ նախադպրոցականի շախմատային նախագիտելիքի ձևավորման գիտատեսական-գործնական բնույթի աշխատանքների կազմակերպման տեսանկյունով: Նախադպրոցականի շախմատային նախագիտելիքը, մի կողմից, զարգացնում է երեխայի իմացական կարողությունները, անձնային կարևոր որակները, մյուս կողմից, ամուր հենք է կրտսեր դպրոցում «Շախմատ» ուսումնական առարկան յուրացնելու համար: Այս իմաստով, ներկայացված է նաև նախագիտելիքի դրական ազդեցությունը նոր նյութի յուրացման, գիտելիքի ձեռքբերման գործընթացի վրա: Հետևաբար, նախադպրոցական կրթական ոլորտի ապագա մասնագետների ձևավորման գործընթացում կարևորվում է ուսումնական փաթեթների վերանայումը և դրանցում շախմատային նախագիտելիքի ներմուծումը: В статье комментируется необходимость пересмотра методик дошкольного образования через научно-теоретическую и практическую работу по развитию предварительных шахматных знаний старшего дошкольника связано с тем простым фактом, что предварительные шахматные знания дошкольника, с одной стороны, способствуют развитию шахматных навыков у старших дошкольников, развитие познавательных способностей ребенка, приобретение важных личностных качеств, с другой стороны, будет прочной основой для легкого восприятия ‗Шахмат‘ в начальной школе. Также обсуждается, в этом смысле, влияние предварительных знаний на процесс восприятия нового материала и приобретения знаний. Поэтому в процессе подготовки будущих специалистов в области дошкольного образования очень важна проверка содержания учебных предметов и введение в них предварительных знаний по шахматам. The necessity to review the methodologies of preschool education through scientific-theoretical and practical work on the development of senior preschooler‘s chess prior knowledge is commented in the article connected with the fact that preschooler‘s chess prior knowledge, on the one hand, contributes to the development of a child's cognitive abilities, acquisition of personal qualities, on the other hand, it will be a solid basis to perceive Chess at elementary classes easily, which is a compulsory subject in Armenian schools. In this context, in the article we also revealed the essence, role, functions, types of prior knowledge on chess. Basing on different definitions on prior knowledge, its interpretations in psychological theories, we can say that prior knowledge becomes the integral part of learning, on which new knowledge, abilities and skills are formed. Hence, we emphasize the formation of preschoolers‘ prior knowledge on chess because, on the one hand, it is reconstructed during learning process, used alternatively and acquired visually, on the other hand, it integrates new information, material with a child‘s previous experience making it reasonable. All these have their positive effect on the process of preschoolers‘ development, where not only the role of an adult but the whole pedagogical process become urgent as well. As it was mentioned we intend to form senior preschoolers‘ prior knowledge on chess through methodologies of preschool education by investing relevant materials in their content (fairy tales, short stories, games, riddles, problem solving tasks, unfinished stories, creating situations, fine art, constructive work ets.). This kind of approach allows to form preschoolers‘ prior knowledge on chess and solve the objectives of a certain methodology at the same time. But the sequence of representing material is also very important: how and by what logical steps we form children‘s prior knowledge, what objectives are solved and what principles are taken into consideration. All these factors have been viewed by us and represented in the article in details.
Keywords: Մանկավարժություն